2016
DOI: 10.1111/jpet.12191
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Growth and Income Inequality under Progressive Taxation

Abstract: This paper develops an endogenous growth model having a progressive income tax structure in which heterogeneous agents, who differ in terms of their rates of time preference, supply labor elastically. We analyze the dynamic adjustment to an increase in progressivity and show that the economy will converge to an equilibrium growth path with nondegenerate distributions of both income and wealth. The role of the endogeneity of labor supply is emphasized and shown to have a major impact on the nature of the transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 51 publications
1
12
0
1
Order By: Relevance
“…In the Appendix, we further prove that if the capital income tax rate is not unduly higher than the labor income tax rate for Group 2 (the rich), the households of Group 1 with higher time preference ρ 1 will eventually become poorer (with a lower total income regardless of before‐tax or after‐tax income) than Group 2, whereas their labor income share is relatively high, which is exactly the result found by Koyuncu and Turnovsky () . As argued by Piketty (, p. 242), inequality with respect to labor usually seems mild and moderate, but inequality with respect to capital is relatively high or even extreme.…”
Section: Macroeconomic Equilibriumsupporting
confidence: 81%
See 2 more Smart Citations
“…In the Appendix, we further prove that if the capital income tax rate is not unduly higher than the labor income tax rate for Group 2 (the rich), the households of Group 1 with higher time preference ρ 1 will eventually become poorer (with a lower total income regardless of before‐tax or after‐tax income) than Group 2, whereas their labor income share is relatively high, which is exactly the result found by Koyuncu and Turnovsky () . As argued by Piketty (, p. 242), inequality with respect to labor usually seems mild and moderate, but inequality with respect to capital is relatively high or even extreme.…”
Section: Macroeconomic Equilibriumsupporting
confidence: 81%
“…Of particular importance, Results 1 and 2 indicate that a reduction in the degree of progressivity of the labor tax can yield a double‐dividend in terms of reducing income inequality and boosting economic growth, while capital income progressivity displays the usual efficiency–equity trade‐off. The conventional notion has indicated that the degree of income progressivity yields a negative relationship between economic growth and income inequality in the model, regardless of whether it has a fixed (Li and Sarte, ) or flexible labor supply (Koyuncu and Turnovsky, ), but the empirical evidence is rather inconclusive. Alesina and Rodrik (), Persson and Tabellini (), and Perotti (1996) find evidence of a negative relationship between inequality and growth, while Partridge (), Forbes (), and Frank () find a positive relationship.…”
Section: Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…20 Raines and Stockman (2010) and Stockman (2010) This paper can be extended in several directions. For example, it would be worthwhile to incorporate multiple production sectors (Meng, 2003;Meng & Velasco, 2004;Weder, 2001), and to consider government expenditure, public debt, and taxes (Huang et al, 2017;Koyunc & Turnovsky, 2016;Morimoto, Hori, Maebayashi & Futagami, 2017; Le Van et al, forthcoming). In addition, I can consider features that are commonly adopted in the new-Keynesian literature, such as price stickiness, wage rigidity, and investment adjustment costs, among others.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of complete congestion, the equilibrium population distribution would be independent of the public expenditure distribution and there would be no role for the public expenditure distribution. 17 See Koyuncu and Turnovsky (2016) for an analysis of the role of labor supply in a growth model. 18 We choose a warm-glow-of-giving utility function merely for analytical simplicity.…”
Section: The Individual Final Income Ismentioning
confidence: 99%